Analysis of the relationship between operating returns and behavioral patterns of corporate leaders - a field study in a sample of Jordanian companies - طلال محمود الججاوي; عبد الخالق الراوي (Iraqi Journal for Administrative Sciences, 2024)
This Research tries to explore the extent of the relationship between operation returns and Corporation Leaders’ Psychological Style after analyzing this relation. Operation returns for nil) corporation reflect accomplishment of employees after deducting expenses (this means the effectiveness of employee’s performance and in the front of this employees are the leaders. Operation return is the main mover to push the corporation to other accomplishments maximize its market value and challenge its competitors. and if assume that other factors fixed except the organizer that shares in production as land, capital, and others then the important factors are the organizer and its efforts, then the role of this organizer is vital and central and very important in the operation returns for any corporation. Organizers as the leaders of corporations are not equal in their Psychological Style that di ide between risk seeker, risk averse, and neutral this Psychological Style is reflected in their administrating of the corporation and finally into operation returns. This research test the general hypothesis: H>: There are statistical relationship between Operation Returns and Corporation Leaders Psychological Style And finally there are main conclusions and recommendations.